Pervasiveness, impact and implications of weight stigma. (May 2022) - Brown, Adrian; Flint, Stuart W.; Batterham, Rachel L.
Summary: Evidence has accumulated to demonstrate the pervasiveness, impact and implications of weight stigma. As such, there is a need for concerted efforts to address weight stigma and discrimination that is evident within, policy, healthcare, media, workplaces, and education. The continuation of weight stigma, which is known to have a negative impact on mental and physical health, threatens the societal values of equality, diversity, and inclusion. This health policy review provides an analysis of the research evidence highlighting the widespread nature of weight stigma, its impact on health policy and the need for action at a policy level. We propose short- and medium-term recommendations to address weight stigma and in doing so, highlight the need change across society to be part of efforts to end weight stigma and discrimination. Funding: None.